KONSEP MENGHADAP NOTARIS DALAM PEMBUATAN AKTA BERDASARKAN PERKEMBANGAN CYBER NOTARY - Christine Willyam Hutapea; Rahmida Erliyani; Anang Shophan Tornado (Collegium Studiosum Journal, 2023)
This research discusses the concept of facing a notary in making a deed based on the development of Cyber Notary. The problem is the development of the concept of facing a notary in the era of cyber notary advancement at this time and policy formulation on the concept of facing a notary in making a deed virtually in the future. The method used is normative legal research with Reform Oriented Research type. The results of the analysis, First, the concept of facing a notary is listed in Article 16 paragraph (1) letter m while Cyber Notary is listed in Article 15 paragraph (3) of the Notary Position Law. The renewal of the concept of facing in the Cyber Notary Era is a consideration of utilizing electronic media by teleconference (virtual). However, when interpreting "in the presence of" article 1868 of the Civil Code is still interpreted conventionally until now. Therefore, the concept of facing has not developed virtually and cannot be done when the explanation of Article 16 paragraph (1) letter m states that "facing" is interpreted as being physically present so that if this formal is not fulfilled, the deed will be relegated to an underhand deed. Second, Policy Formulation of the concept of facing virtually in the future can be applied by considering what can be done in the authority and obligations of notaries. With technology everyone can face virtually. In the notary profession this can be applied by reforming the Laws and Regulations on Notary Position. Not only conventional facing but virtually using applications and sticking to the principle of prudence, so that the meaning of Virtual Facing can be applied in the concept of Cyber Notary in Indonesia.